Diagnosis and Management of Cerebral Vasospasm Following Aneurysmal SAH - Oktavian, Mirza; Bisri, Dewi Yulianti; Rachman, Iwan Abdul (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Cerebral Vasospasm, characterized by the progressive constriction of cerebral arteries, often occurs following a subarachnoid hemorrhage (SAH) and is a leading cause of morbidity and mortality in affected patients. This condition can be resulted in cerebral ischemia, the severity of which correlates with the degree of vasospasm. The underlying pathophysiology involves the encasement of arteries by blood clots, although the intricate interactions between the hematoma and adjacent structures remain incompletely understood. The delayed onset of vasospasm offers a potential window for preventive interventions. However, recent randomized controlled trials have been discouraging, as they failed to demonstrate any significant improvement in patient outcomes with the use of clazosentan (an endothelin antagonist), simvastatin (a cholesterol-lowering agent), or magnesium sulfate (a vasodilator). Current best practices for managing vasospasm include minimizing ischemia by maintaining adequate blood volume and pressure, administering nimodipine (a calcium channel blocker), and, when necessary, performing balloon angioplasty. Over the past two decades, advancements in the management of vasospasm have significantly reduced associated morbidity and mortality rates. Nevertheless, vasospasm remains a critical determinant of clinical outcomes following aneurysmal rupture.